FLAVONAS METOXILADAS DE TRES ESPECIES DEL GENERO EUPATORIUM - Torrenegra, Rubén D.; Grupo de Investigación Fitoquímica (GIFUJ), Departamento de Química, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (Pontificia Universidad Javeriana, 2013)
Five methox:ylated flavones were isolated from aerial parts of three species of Eupatorium. The extracts from flowers and leaves of E. micropillum and E . . l'iscosum affored 5-hidrox:y-6,7,3',4'- tetramethox:y flavone and" . 7,8,3',4'-tetramethox:y flavone. The flowers of R gracile gave three flavonoids: 3,5,4' -Three hydroxy- 7,8-dimethoxy flavori.e, methox:y flavone, and 3,5,7,4'-tetrahydrox:y-8-methox:y flavone.